GAMBARAN PELAKSANAAN KOMUNIKASI TERAPEUTIK DI RUANG RAWAT INAP RSUD KECAMATAN MANDAU DURI - Helmizan " "; Darwin " "; Oswati " Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Therapeutic communication is communication that have therapeutic meaning for the patient and performed by nurses (helper) to help patients regain the adaptive and positive conditions. This study aimed to describe the implementation of therapeutic communication in Mandau Duri public hospital. The design of the research was descriptive research. Samples were 30 respondents who were taken based on inclusion criteria by using purposive sampling technique by observing the inclusion criteria. The instrument used was the observation sheet. The analysis used was univariate analysis. The results showed the description of the implementation of therapeutic communication that the majority of respondents do therapeutic communication in the orientation phase, all nurses were obtained perform therapeutic communication in the working phase, and in the termination phase was also obtained all nurses perform therapeutic communication as well as do attitude therapeutic communication. The result described the implementation of therapeutic communication in the orientation phase was not maximally done by nurses. The results of this study recommended any nurses in order to increase the efforts of therapeutic communication implementation, as well as to follow seminars to know more about therapeutic communication.